The English Chorister: A History - Mould, Alan (London Continuum, 2007)
Choral training and singing in cathedrals and other churches has been at the heart of the English musical tradition, with many leading musicians originally trained as choir boys. The English Chorister is a history going back to medieval times of how singers were recruited and educated, showing the changes in approach over the centuries, particularly after the Reformation. The great cathedrals provided the setting for the performance, as well as often the composition, of some of the greatest English music, from Taverner to Byrd and from Purcell to Parry. Despite major threats during the Civil War and the eighteenth century, choral singing blossomed under the Victorians. It is a still a strong tradition, if changed in recent years by the addition of girls to almost all choirs. >
Keywords: Choir; Singing; Choral music; Music history; United Kingdom